High performance scheduler for multicast switches. (2018) - Prasanth, N. Narayanan; Devi, R. Chithra; Raja, S.P.
Day-by-day, the desideratum for high speed internet connectivity increases and consequently, high performance switches are imminent. These switches require efficient schedulers to reach its maximum potential. In this paper, a high performance scheduler is proposed for buffered crossbar switches to work under multicast traffic. The scheduler is able to reduce the starvation effect and thereby achieves maximum throughput with minimum delay than existing algorithms.